Hi hi hi hi hi hi hi hi The answer is D
Y=-5/3x+1
I hope this helps!
The equation of function g(x) in terms of f(x) is g(x) = -3[f(x)].
<h3>What is an equation?</h3>
An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
Given:
genera form of an exponential function is y=aeᵇˣ
Now, equation for f(x) is
f(x) = ![e^{(log \;2)x} -2](https://tex.z-dn.net/?f=e%5E%7B%28log%20%5C%3B2%29x%7D%20-2)
Similarly, graph for g(x) is
g(x) = ![-3e^{(log \;2)x} +6](https://tex.z-dn.net/?f=-3e%5E%7B%28log%20%5C%3B2%29x%7D%20%2B6)
Comparing the two function a relation can be establish
g(x) = -3[f(x)]
Learn more about Equation here:
brainly.com/question/2263981
#SPJ1
Answer:
8x + 5
Step-by-step explanation:
By adding
2x + 6 + 6x -1
8x + 5
I would say it is 4(6+11) that or 72 is the answer